SEARCHES OF RESEARCH WAYS OF CHINESE-FAR EASTERN WORLD OF CIVILIZATION - Михайлов, В. С. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article explored the genesis of the concept of "civilization" and civilized approach in the light of the need to understand the essence of Chinese civilization of the Far Eastern world. -depth research.